Prevalence of Cotton Leaf Curl Virus Disease in North-West Part of Rajasthan and its Management - Sharma, R. N.; Gaur, R. B.; Singh, V. (International Journal of Economic Plants, 2021)
Field survey to find out the severity of cotton leaf curl virus (CLCV) disease was undertaken during the year 2009. The cotton fields of 62 villages/ Chaks covering 7 tehsils of Sriganganagar and 7 tehsils of Hanumangarh district were surveyed which comprises North-West part of Rajasthan, India. Severe attack of CLCV (6.3–100%) in Sriganganagar tehsil; moderate attack (0–32.3%) in Srikaranpur, Sangaria and Hanumangarh tehsil; low level (0–10.8%) attack in Sadulsahar, Tibi and Nohar tehsil and traces level (0–5.7%) attack in Bhadra, Anupgarh, Raisinghnagar, Padampur and Suratgarh tehsil was observed. Further, a field trial was also laid out at ARS, Sriganganagar for the management of disease for two consecutive years (2010 and 2011). Minimum disease intensity (31.5%) and maximum reduction in disease intensity (37.5%) over control were observed in the foliar treatment of Acephate 60% WP + Kresoxim methyl 15% WG (750+187.5 g a.i. ha-1) followed by Buprofezin 25% SC (250 g a.i. ha-1). Acephate 75% SP (750 g a.i. ha-1) provided 34.9 and 33.7% protection from the disease as compared to control.